If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -7 = -23 Reorder the terms: -7 + 2y = -23 Solving -7 + 2y = -23 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 2y = -23 + 7 Combine like terms: -7 + 7 = 0 0 + 2y = -23 + 7 2y = -23 + 7 Combine like terms: -23 + 7 = -16 2y = -16 Divide each side by '2'. y = -8 Simplifying y = -8
| (3/4w)-5=(1/4w)-1 | | 8x+6=-26 | | -2a+3T=24 | | g-2/3g=-5/6 | | 3(2n)+1=25 | | -21=4(9n+7) | | 9x+8-8x=12 | | 3(2)+1=25 | | 48/40 | | 3p-1=5(p-1)-2(7+2p) | | 3x+7+6=-22 | | n/9=4.4 | | 6x-4y=54 | | 203-5x=31x+19 | | 15/24*16/25= | | 12c+7=10c+1 | | 5x-8-3x=12-2x+8x | | v-3.5=3.3 | | 1/2(4d)+2=130 | | -4.9=d-5.8 | | 2x+12x=16x+10 | | f/5=4.8 | | x^6-7x^3+12=0 | | 13x=14x-10 | | -3z-12=-4z | | -7x+3+2=-8x-8 | | -8+20=m-1 | | 30.6=3.4k | | 1-5y=y-3 | | 3h=9 | | -7/9a=77 | | 14x-1=13x+4 |